THE COMPARATIVE EFECTIVENEESS OF USING THE LIVESTOOK URINEIN MAKING LIQUID ORGANIC FERTILIZER ON GREEN BEAN THROUGH VEGETATIF GROWTH (Vigna radiata) IN EFFORTS BROCHURE OF SOCIETY - I Made Asta; Iwan Doddy Dharmawibawa; Sucika Armiani (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2016)
ABSTRACT: The purpose of this research is to comparing effectiveness of cattle urine as a organic manure on the vegetative growth of green beans (Vigna radiata) and attemp to design a brochure for the people. Research design used in this research is complete random design (CDR). The data collected in this research were obtained using observation and documentation techniques, than that the datum analyzed with one way anova. The sample consit of 4 tratments with the same dosage that is 40 ml/kg of soil and each tratements repeated 6 times. The parameters observed I this research is the plant height, stem diameter, number of leaves, fresh weight, and dry weight. The result of the research on plant height, number of leaves, fres and dry weight of plants showed significant value, while the paramaters of stem diamter showed no significant result. Based on the result of the research show that P1 (treatment using rabbit urine) showed the best result among the parameters plant heigh and the number of leaves.In P2 (treatment using goat urine) giving the best result on the fres and dry weight paramaters of green bean plant. From observation of the fifth parameters, there are four parameters show that rsignificant result, that is plant heigh, number of leaves, fresh and dry weight of green bean, but there are one paramater that has no significant result (no effect), that is stem diameter of green bean.